Prospective Public Education in The Era of Digitalization Through Content Creators - Deona, Salsabila; Trigunawan, Ivan; Mukhti, Berlina (Universitas Negeri Padang, 2024)
The era of digitalization has brought significant changes to various aspects of life, including education. Advanced communication technology enables the rapid and widespread dissemination of information, particularly through social media. This makes non-formal education increasingly accessible to the public, thanks to educational content created by content creators. This article uses a literature review method to explore the prospects of public education through content creators in the digital era. The results show that content creators can provide wide accessibility and reach, flexibility in access, collaboration with various institutions, and creativity in presenting educational content. However, challenges such as the technology access gap, content quality and accuracy, information overload, and data security and privacy need to be addressed to maximize the benefits of education in this digital era. Collaboration between content creators and educational institutions can enhance the quality of content, while creativity in content presentation is also crucial to attract public interest. Keywords: Public Education, Content Creator, Digital Era